Tendencies for the falsification of medicinal products in Ukraine: general analysis and areas of counteraction - Логвиненко, Борис Олексійович; Логвиненко, Б. О.; Логвиненко, Борис Алексеевич; Lohvynenko, Borys O.; Сезонов, Віктор Станіславович; Сезонов, В. С.; Сезонов, Виктор Станиславович; Sezonov, Viktor S.; Француз-Яковець, Тетяна Анатоліївна; Француз-Яковець, Т. А.; Француз-Яковец, Татьяна Анатольевна; Frantsuz-Yakovets, Tetiana A. (Aluna Publishing, 2019)
Objective: Introduction: Ukrainian counterfeit pharmaceutical market affects pharmaceutical manufacturers' image and threatens citizens' lives and health. The aim:of the article is to identify and systematize the causes and methods of pharmacy drugs' falsification, grounding the need for certain areas of counteraction. Patients and methods: Materials and methods: Empirical base includes Ukrainian legislation, international acts, statistical data of the WHO, State Register of Medicinal Products of Ukraine, General Prosecutor's Office of Ukraine, Unified State Register of Court Decisions, media materials, journalistic investigations. Methodological basis is a set of general and special research methods of scientific cognition. Conclusion: Conclusions: Expired drugs' repackaging; production in non-licensed enterprises; replacement of drugs by non-pharmacological substances, etc. were established as the most common methods of falsifying pharmacy drugs in Ukraine. The authors systematized the reasons for uncontrolled production's growth, established distribution channels for pharmacy drugs in Ukraine and offered the most effective ways for counteracting drug falsification.

Український ринок контрафактної фармацевтичної продукції впливає на імідж виробників фармацевтичної продукції та загрожує життю та здоров'ю громадян. Метою статті є виявлення та систематизація причин та способів фальсифікації аптечних ліків, обґрунтування необхідності окремих напрямів протидії. Емпірична база: законодавство України, міжнародні акти, статистичні дані ВООЗ, Державний реєстр лікарських засобів України, Генеральної прокуратури України, Єдиний державний реєстр судових рішень, матеріали ЗМІ, журналістські розслідування. Методологічна основа — це сукупність загальних і спеціальних методів дослідження наукового пізнання. Висновки: переупаковка ліків із простроченим терміном придатності; виробництво на неліцензованих підприємствах; заміна ліків нефармакологічними речовинами тощо утвердилися як найпоширеніші методи фальсифікації аптечних ліків в Україні. Автори систематизували причини неконтрольованого зростання виробництва, налагоджені канали збуту аптечних ліків в Україні та запропонували найефективніші способи протидії фальсифікації ліків.
Lohvynenko B. O. Tendencies for the falsification of medicinal products in Ukraine: general analysis and areas of counteraction / B. O. Lohvynenko, V. S. Sezonov, T. A. Frantsuz-Yakovets // Wiadomosci lekarskie (Warsaw, Poland : 1960). - Tom 72 (12 cz 2). - Aluna Publishing, 2019. - Р. 2478-2483.
Keywords: methods of commission; falsification; causes; counteraction; pharmacy drugs; способи комісії; фальсифікація; причини; протидія; аптечні препарати; Research Subject Categories::LAW/JURISPRUDENCE